2020
DOI: 10.1038/s41598-020-65106-w
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the global distribution and diversified plasmid reservoirs of the colistin resistance gene mcr-9

Abstract: The emergence and spread of mobilized colistin resistance (mcr) genes have triggered extensive concerns worldwide. Here, we characterized the global distribution of mcr-9, a newly-identified variant of mcr, by assembling the data set of mcr-9-positive isolates from GenBank database and the literature available. Genetic features of all the mcr-9-harboring plasmids were determined by bioinformatic analysis. We showed that mcr-9 is globally distributed in 21 countries across six continents, with a wide disseminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
99
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(111 citation statements)
references
References 26 publications
9
99
0
3
Order By: Relevance
“…1). Consistently, a recent report identi ed that IncHI2-type plasmids may serve as a critical reservoir of mcr-9 (22). Blasting the sequence of pECL-90-2 in GenBank database showed the best matches were plasmid pGW1 carried by a Cronobacter sakazakii strain GZcsf-1 (CP028975, 86.8% query coverage and 99.99% sequence identity) and plasmid p17277A_477 carried by a Klebsiella quasipneumoniae subsp.…”
Section: Genome Contentsupporting
confidence: 63%
See 1 more Smart Citation
“…1). Consistently, a recent report identi ed that IncHI2-type plasmids may serve as a critical reservoir of mcr-9 (22). Blasting the sequence of pECL-90-2 in GenBank database showed the best matches were plasmid pGW1 carried by a Cronobacter sakazakii strain GZcsf-1 (CP028975, 86.8% query coverage and 99.99% sequence identity) and plasmid p17277A_477 carried by a Klebsiella quasipneumoniae subsp.…”
Section: Genome Contentsupporting
confidence: 63%
“…This is consistent with the previous report that mcr − 9.1 is inactive in colistin resistance (21). A recent study with global data revealed that Enterobacter spp., was the predominant host of mcr-9 (37%) (22).…”
Section: Genome Contentmentioning
confidence: 99%
“…The mcr-9 gene was first reported in a clinical Salmonella Typhimurium isolate in the USA in May 2019 (24). Isolates harboring mcr-9 were subsequently identified in 21 countries covering six continents, including Europe, Asia, America, Oceania, South America, and Africa (27). An mcr-9 harboring Enterobacter hormaechei isolate obtained from the sputum of a patient in Cairo, Egypt, is to date the only mcr-9 positive isolate reported in Africa (28).…”
Section: Discussionmentioning
confidence: 99%
“…Following the first description, several reports describing the presence of mcr-1 in different host species and geographic areas were published ( 7 , 8 ). Thus far, the mcr gene family comprises mcr-1 to mcr-10 ( 9 ). These genes encode phosphoethanolamine transferases that catalyze the addition of phosphoethanolamine to the phosphate group of lipid A, reducing the negative charge of the bacterial outer membrane and attenuating its affinity for colistin, resulting in antibiotic resistance.…”
Section: Observationmentioning
confidence: 99%
“…The mcr-9 gene has been identified from 40 countries across six continents. However, half of mcr-9 -positive isolates (1,035/1,682 strains) were recovered in the United States, among which Salmonella enterica was the most common host species, especially in turkeys and chickens ( 9 ).…”
Section: Observationmentioning
confidence: 99%